Unlocking Bilingual Literacy: A Tech-Driven Approach to English Writing and Translation - Irawati, Tatik; Puspitasari, Yunita; Fatrisyah, Meisy; Zahroh, Fatimatuz (Universitas Muhammadiyah Mataram, 2025)
Using the socio-cognitive and CLT theoretical frameworks as lenses, this research investigates the implementation of technology-integrated learning tools to enhance bilingual literacy, specifically in English writing and translation. Employing a mixed-method descriptive design, the study involved 120 students from four Grade XI at SMKN 1 Jombang. Data were collected via online questionnaires containing both closed- and open-ended items. The results demonstrate that students frequently utilized applications such as Google Translate and Grammarly, particularly during the editing, revising, and meaning clarification stages. The majority acknowledged substantial improvements in lexical selection, grammatical precision, and translation comprehension. Despite this, several constraints were identified, including unstable internet access and limited familiarity with specific tools, underscoring the need for systematic support and instructional scaffolding. This study makes a pedagogical contribution by presenting an integrative framework that unites writing and translation within a technology-enhanced language-learning environment. The findings affirm the relevance of such an approach for vocational education settings, where practical communication skills are critical for both academic achievement and workforce readiness.